2020
DOI: 10.2147/copd.s278981
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics Associated with Accelerated Lung Function Decline in a Primary Care Population with Chronic Obstructive Pulmonary Disease</p>

Abstract: Background: Estimates for lung function decline in chronic obstructive pulmonary disease (COPD) have differed by study setting and have not been described in a UK primary care population. Purpose: To describe rates of FEV 1 and FVC decline in COPD and investigate characteristics associated with accelerated decline. Patients and Methods: Current/ex-smoking COPD patients (35 years+) who had at least 2 FEV 1 or FVC measurements ≥6 months apart were included using Clinical Practice Research Datalink. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…Previous studies have investigated how patient characteristics are associated with FEV 1 decline; however, the purpose of this study was to primarily show how mean rates of FEV 1 decline differed depending on the definition used. [8][9][10]20,21 We found that in the cohorts that did not exclude measurements or individuals due to increases in FEV 1 , the mean rates of FEV 1 and within patient variation remained similar. For this reason, the definition used to create population one (i.e., using all available FEV 1 measurements over follow-up) could be used to describe the rate of FEV 1 decline in a COPD population using CPRD data.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies have investigated how patient characteristics are associated with FEV 1 decline; however, the purpose of this study was to primarily show how mean rates of FEV 1 decline differed depending on the definition used. [8][9][10]20,21 We found that in the cohorts that did not exclude measurements or individuals due to increases in FEV 1 , the mean rates of FEV 1 and within patient variation remained similar. For this reason, the definition used to create population one (i.e., using all available FEV 1 measurements over follow-up) could be used to describe the rate of FEV 1 decline in a COPD population using CPRD data.…”
Section: Discussionmentioning
confidence: 64%
“…The mean annual rates of FEV 1 decline described in this study for populations one and three to eight were similar to those reported in previous studies of COPD patients. 4,8,9 Interestingly, population two (those who were excluded due to potential measurement error) had faster rates of FEV 1 decline. More patients with low FEV 1 % predicted were excluded in this population, which meant that there were more patients with milder COPD (higher FEV 1 % predicted) than all other populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, age does not seem to have a significant effect on response to treatment. This jeopardizes the traditional idea that COPD unquestionably progresses with age, in other words, that the older the lung function, the weaker the response to single bronchodilation [ 22 ]. In line with other previous authors, our data contradict this view of the disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides demographic risk factors, including a higher age, a lower body mass index (BMI), being a current smoker, and more severe dyspnea (11,14), frequent or acute exacerbation events are important risk factors for the rapid decline in lung function (15)(16)(17). Recent studies indicate that acute exacerbation and a rapid decline in FEV 1 are related with high counts of blood eosinophils (18).…”
Section: Introductionmentioning
confidence: 99%